Gap analysis on accident causation and implementation of Integrated Management System (IMS) at construction site / Azmi Che Leh, Asmalia Che Ahmad and Ahmad Qusoiri Abdul Karim - Che Leh, Azmi; Che Ahmad, Asmalia; Abdul Karim, Ahmad Qusoiri (2021)
The current high fatality rate in construction accidents negatively reflects the nation’s construction industry. This research aims to identify the main causes of accidents and the gap between the causes of the accident that would allow for solutions to minimise the fatality rate. Systematic Literature Review was conducted to review past studies on accident causation and the benefits of Integrated Management System (IMS) in managing the safety of construction workers. Scopus and Web of Science were referred to as the source database. 23 journal articles were indicating that human factors are the leading cause of accidents. 35 journal papers discussed on IMS which provides various benefits. Therefore, it is suggested that human factors should be incorporated with IMS knowledge towards minimising the fatality of the construction workers.